2011
DOI: 10.1002/ajmg.b.31238
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in repetitive stereotyped behaviors in autism: Implications for genetic liability

Abstract: The implications of the well known sex differences in the prevalence of autism spectrum disorder (ASD) are not well understood. The aim of this paper was to investigate whether these differences might be associated with differences in genetic liability. Individuals with ASD (970 families, 2,028 individuals) were recruited as part of the Autism Genome Project (AGP). The families were differentiated into families containing a female (either female-female or male-female) and those with only males. If the sex with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
141
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(162 citation statements)
references
References 41 publications
19
141
1
1
Order By: Relevance
“…Sex differences in the typical population were also attenuated in males and females with ASD ( Baron-Cohen et al, 2014), which is in line with a recent meta-analysis revealing only minor differences between ASD males and ASD females in the domain of social behavior and communication (Van Wijngaarden-Cremers et al, 2014). In the domain of repetitive and restricted behaviors on the other hand, reductions in females compared to males have been consistently reported (Mandy et al, 2012;Szatmari et al, 2012;Frazier et al, 2014;Van Wijngaarden-Cremers et al, 2014).…”
Section: Introductionsupporting
confidence: 85%
“…Sex differences in the typical population were also attenuated in males and females with ASD ( Baron-Cohen et al, 2014), which is in line with a recent meta-analysis revealing only minor differences between ASD males and ASD females in the domain of social behavior and communication (Van Wijngaarden-Cremers et al, 2014). In the domain of repetitive and restricted behaviors on the other hand, reductions in females compared to males have been consistently reported (Mandy et al, 2012;Szatmari et al, 2012;Frazier et al, 2014;Van Wijngaarden-Cremers et al, 2014).…”
Section: Introductionsupporting
confidence: 85%
“…However, there is a great deal of literature concerning the varying profile of autism as expressed by gender differences and the vast majority of studies have been conducted with predominantly male samples (Bell et al 2005). Furthermore, the available findings on the differences in clinical profiles between males and females with ASD have J Autism Dev Disord (2015) 45:2046-2055 2049 Table 1 ADOS severity score, GMDS-ER and VABS-SF at T0 and T1 Autism Dev Disord (2015) 45:2046-20552051 shown contrasting results (Carter et al 2007;Banach et al 2009;Andersson et al 2013;Van Wijngaarden-Cremers et al 2013;Hofvander et al 2009;Lugnegard et al 2011;Matson and Nebel-Schwalm 2007;Park et al 2012;Simonoff et al 2008;Lai et al 2011;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012;Szatmari et al 2012;Donna et al 2013). On the one hand, most studies found no gender differences on social behaviors or communication nor on RRB (Carter et al 2007;Banach et al 2009;Andersson et al 2013;Hofvander et al 2009;Lugnegard et al 2011;Matson and Nebel-Schwalm 2007;Park et al 2012;Simonoff et al 2008;Lai et al 2011;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies failed to find any differences in the core symptoms of ASD between males and females (Carter et al 2007;Banach et al 2009;Andersson et al 2013;Mayes and Calhoun 2011;Zwaigenbaum et al 2012;Mandy et al 2012;Szatmari et al 2012;Donna et al 2013). On the other hand, a meta-analysis of 20 studies investigating gender differences in ASD reported few differences in symptom severity between males and females.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that first-degree relatives of autistic females have more ASD symptoms than first-degree relatives of autistic males [30][31][32]. Nevertheless, these findings have been contradicted, with one study showing no greater likelihood of ASD amongst relatives of autistic females [33].…”
Section: Female Protective Effectmentioning
confidence: 99%